2021
DOI: 10.1016/j.parepi.2021.e00209
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Trypanosoma evansi in camels using CATT/T. evansi technique in Borno and Yobe states, Nigeria

Abstract: Trypanosoma evansi is an important camel pathogen with dissimilar mammalian hosts and is the most widely distributed pathogenic animals' trypanosomes worldwide that affects domesticated animals. Four hundred and six blood samples were collected using homogeneous purposive sampling techniques from camels of all age groups (206 from Borno State and 200 from Yobe State, Nigeria). Each animal was examined and information on age and gender were recorded. The card agglutination test for T. eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…On the other hand, the animal level seroprevalence of T.evansi in Tunisia was higher than those reported in previous studies carried on Morocco (14.1%), Mauritania (Trarza, Gorgol, Adrar, Hodh El Chargui and Nouakchott) (16.2%), and Ethiopia (between 13.7% and 24.1%) ( Atarhouch et al, 2003 ; Birhanu et al, 2016 ; Dia et al, 1997 ; Fikru et al, 2015 ). High seroprevalence of T.evansi was recorded also in Nigeria (44.09%), Kenya (45.9%), and Egypt (82%) which is in contrast with our result ( Kyari et al, 2021 ; Njiru et al, 2004 ; Zayed et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the animal level seroprevalence of T.evansi in Tunisia was higher than those reported in previous studies carried on Morocco (14.1%), Mauritania (Trarza, Gorgol, Adrar, Hodh El Chargui and Nouakchott) (16.2%), and Ethiopia (between 13.7% and 24.1%) ( Atarhouch et al, 2003 ; Birhanu et al, 2016 ; Dia et al, 1997 ; Fikru et al, 2015 ). High seroprevalence of T.evansi was recorded also in Nigeria (44.09%), Kenya (45.9%), and Egypt (82%) which is in contrast with our result ( Kyari et al, 2021 ; Njiru et al, 2004 ; Zayed et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 99%
“…More than half of studied animals (57.1%) were seropositive for T. evansi by CATT which is similar to those recorded by Benaissa et al (2020) in south Algeria (45,9%), Kyari et al (2021) in Kenya (45.9%) and Njiru et al, (2004) in Nigeria (44%). While, it was higher than that found by Kalthoum et al (2022) in Tunisia (30.8%), Boushaki et al (2019) in Algeria (32.4%), Atarhouch et al (2003) in Morocco (16%) and Dia et al (1997) in Mauritania (14.2%).…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, previous reports found that T. evansi infection or seropositivity were higher on adult camels (> 4 years) than young ones 5 , 13 , 39 . However, other studies have found a higher rate of T. evansi infection in young camels 33 , 40 and no association between of T. evansi infection and camel age 41 , 42 . The high risk of T. evansi infection in older camels could be attributed to the chronic nature of the disease and intermittent parasitaemia, poor management and stress associated with the use of camels in draught.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the PCR estimated prevalence in the present study was higher than 11.2% reported in camels from South Algeria 5 , but lower than the 30% 32 and 31.9% 12 reported in camels from Palestine and Pakistan, respectively. The variation in the T. evansi prevalence could be attributed to sample size, sampling technique and vector density in the study area 33 . The significant difference in proportion of positivity determined by each test is expected and is consistent with previous study in camels from Kenya 34 .…”
Section: Discussionmentioning
confidence: 96%